Censorship, Resistance and Transformation in Modern Indonesian Literature - Ferdinal, Ferdinal (Richtmann Publishing, 2013)
This paper investigates the way in which Indonesian literature has reflected violations of human rights in Indonesia in the lastdecade of the New Order (1990-1998). The regime was authoritarian and responded harshly to any challenge which couldcause trouble to national stability. Some writers, such as Seno Gumira Ajidarma, used the power of allegory to resist thisoppression. The three works examined here – ‘Saksi Mata’, ‘Pelajaran Sejarah’, and ‘Misteri Kota Ninggi’ – can be consideredas a form of resistance literature.